O wielostronności, relatywizmie i złożoności kategorii efektywności - Rybicki, Wojciech (On Many-Sideness, Relativity and Complexity of the "Efficiency" (As a Category), 2005)
The paper is devoted to discuss many-sided aspects of the notion "efficiency". At the same time we review some typical particular cases (situations) when this word (notion) appears. Efficiency plays a crucial role in a variety of contexts. So, it should be treated as a fundamental praxeological category. On the other hand (somewhat paradoxically) the above mentioned its manysideness makes difficult to determine "universal", the "only proper" meaning of this term. Nevertheless one may try to search (and suggest) some reasonable, unquestioned ways of interpretation of this notion. We start from remembering a latin root-word of this term - it seems to be necessary, from methological point of view. Next we propose to distinct three forms of meaninig of this wored: efficiency sensu stricte , efficiency as an efficacy and efficiency as a "reality". In the second proposed classification we point out the fact that efficiency is a property of something: it must be related to the concrete enterprise (it does not function independently on any object, process, system or program). We introduce the following "kinds" of efficiency: (i) efficiency in a "physico-biological" sense. The essence of such meaning of efficiency is its qualitative rather than quantitative character. It can be associated with such notions as survival or feasibility of actions or tasks; (ii) efficiency in a "mathematical and economic" sense. Roughly speaking, in this case we think about the quantitative index, which serves to measuring or comparing of grade of intensity appearing feature or process; (iii) efficiency in a "constructive and cooperative" sense. In this case we appreciate such points as management and organization of enterprises. We explain all the above mentioned terms in detail. At a further part of the paper we provide examples from general theory of rational behaviour, theory of investment (which, in turn, constitutes a core of economic activity), some classical models of microeconomics as well as macroeconomic theory. We also note cybernetical aspects of efficiently acting systems. It is also worth to mention numerous examples of presence this term in other fields: mathematical economics, econometrics and forecasting, theory of games, statistical decisions, operation researches, insurance, financial mathematics, reliability and quieuing theory. Generally, efficiency is associated and stricly connected with such notions as rationality, optimization and equilibrium. We conclude presented essey with somewhat spitefull statements: (almost) everybody feels that efficiency significantly influences wealth and welfare (of individuals, firms and nations), all scientists as well as practicioners agree about its importance in economic area but nobody knows its precise definition, because such a definition does not exist.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 358-382